Sensory profile of five superior salak varieties in Indonesia: Profil sensori lima varietas salak unggul di Indonesia - Siregar, Lerissa Aulia; Adawiyah, Dede Robiatul; Hunaefi, Dase (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2025)
Salak (Salacca zalacca) is a tropical fruit widely consumed in Indonesia. The fruit has scaly skin resembling snake scales, often referred to as snake fruit. This study aimed to describe consumer preferences through the sensory characterization of five superior salak varieties: Madu, Pondoh, Gading, Gula Pasir, and Sidempuan, using the Rate-All-That-Apply (RATA) sensory method and a hedonic rating test. The results showed that salak Madu was characterized by sweet, salak ID (typical salak aroma), juiciness, and mealy attributes. Salak Pondoh was described as sweet, fruity, floral/perfumy, and cohesive of mass. Salak Gula Pasir had sensory attributes such as crispness, firmness, chemical, and grittiness. Meanwhile, salak Gading and Sidempuan shared similar sensory profiles, including green, starchy, peel-like, fermented, sour, bitter, and astringent attributes. Salak Madu received the highest preference level, presumably due to its dominant sweet taste. Conversely, salak Sidempuan and Gading showed lower acceptance levels because of their high sourness and astringency intensities. Overall, varieties with sweet taste profiles, such as Madu, Pondoh, and Gula Pasir, aligned better with panelists' preferences than those with dominant sour and astringent characteristics, such as Gading and Sidempuan. These findings have important implications for product development and marketing strategies, particularly in selecting salak varieties that meet consumer preferences for fresh consumption and differentiation in processed products.